KEEFEKTIFAN ALAT BANTU AJAR LOW-COST PADA PEMBELAJARAN KLINIS AKDR - Tombokan, Sandra G.J. (Asosiasi Pendidikan Kebidanan Indonesia, 2018)
Teaching aids in clinical learning in midwifery education are essential. However, not all tools manufactured and sold meet the low-cost quality standard. The IUD insertion and disposal aids tool has been created by JM Metha by modifying the already-sold-out tools for the purposes of the previously mentioned clinical learning. Therefore, this study is intended to prove that the Metha tool meets three criteria of realistic, durable, and inexpensive teaching aids in addition to being safe because they are made of non-hazardous fabrics.